A Numerical Study on the Impact of Vehicles' Blockage on the Performance of Semi-transversal Smoke Control System in Tunnel Fire. (2016) - Lin, Peng; Zhang, Yu-cun; Li, Tao; Si, You-liang
Abstract: In this paper, numerical simulations are conducted to investigate the impact of the blockage of vehicles in tunnel on the performance of semi-transverse smoke control system. Two well-known CFD tools, i.e., FDS 6.0.1 and ANSYS FLUENT 14, are used for mutual verification. The smoke pattern in tunnel without blockage is studied as a benchmark and the proposed semi-transverse smoke control system can maintain tenable conditions for safe egress. The scenarios with blockages of 2m and 4m high are studied respectively. The simulation results demonstrate the presence of blockage significantly changes the flow pattern in tunnel. The bulk mass flow rates are reduced from the blocked side while increased from the unblocked side. The unbalanced airflow drives more smoke to the blocked side and makes this side impassable for evacuation within a few minutes. The scenarios with symmetric blockages of the same heights are further studied for comparison and smoke is well confined within the defined smoke zone. Tentative simulations are conducted to improve the environment in tunnel by increasing the smoke extraction rate. For a blockage ratio of 26.6%, even a 50% increase in the smoke extraction rate can hardly maintain tenable condition throughout the tunnel.